Pseudo-semi-solid thixoforging of cup shell with Al/Al2O3 - 罗守靖 程远胜 王鹏翔 (Transactions of Nonferrous Metals Society of China, 2006)
A new technology-the thixoforging of ceramics/metal composites in pseudo-semi-solid state was proposed based on the powder metallurgy technology combined with semi-solid metal forming process, and the cup shell of automobile piston with Al2O3/Al composites was prepared. It is proved through metallographic analyses and three-point bending tests that the technology is feasible for the ceramics/metal composites forming. The results show that the tough strength and the degree of hardness of the samples with certain plasticity are high. It will play a very large role in accelerating the ceramics composites and high melt point materials use in more fields and tamp the foundation for further studies of this technology.